EVALUASI PENJADWALAN MAINTENANCE A/E (AUXILIARY ENGINE) TYPE YANMAR 6KHL-STN, MV.MERATUS SABANG DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE - Zendy Reda Rhomadan; Muhammad Shah; Nurvita Arumsari (Politeknik Perkapalan Negeri Surabaya, 2023)
Identification of the level of criticality of a component based on the Reliability Centered Maintenance II method obtained components that have a critical level quantitatively owned by components in the F.O fuel system transfer pipe from injector pump to injector with a value of R(t) = 76 if qualitatively assisted with FMEA results the highest is owned by the fuel system component with RPN value = 150. and cost comparison analysis after implementing maintenance using Reliability Centered Maintenance II. Later, it is hoped that the results of this proper maintenance program can be applied to the Auxiliary Engine MV. Meratus Sabang in order to minimize operational costs that will be used in the future.